Social Motives and Group Commitment on Volunteer Involvement in Five Social Communities in The City of Bandar Lampung - Fitriani, Annisa; Rasyidin, Yusafrida; Irawan, Yoga; Zalmansyah, Achril (ANFUSINA: Journal of Psychology, 2023)
AbstractVolunteers are people who decide to be involved in volunteering activities based on careful calculation. The activities by volunteers are voluntary and without expecting external rewards. The population in the study came from five social communities in Bandar Lampung: 1) Jendela Lampung Community, 2) Komunitas Peduli Generasi with Yayasan Rumah Singgah Peduli Lampung, 3) Komunitas Sedekah Lampung, 4) Komunitas Berbagi (Kombi), and 5) Itera Mengajar. From these five social communities, the researchers obtained a population of 202 volunteers. The researchers obtained a sample of 60 volunteers through purposive sampling techniques and screening. This study employed Likert scales data collection method, which includes a volunteer involvement scale, a social motive scale, and a group commitment scale. The data were analyzed using two predictor multiple regression analysis techniques assisted by the JASP 0.16.1.0 program for Windows. The results showed that the correlation value (r) was 0.337 with a significant p-value of 0.041 (p-value smaller than 0.05). The hypothesis is accepted; therefore, a significant relationship exists between social motives and group commitment on volunteer involvement. The R2 value of 0.155 states that the two independent variables effectively contribute 15.5%.Keywords: Volunteer Involvement, Social Motives, and Group Commitment